Considering new methodologies in strategies for safety assessment of foods and food ingredients. (May 2016) - Blaauboer, Bas J.; Boobis, Alan R.; Bradford, Bobbie; Cockburn, Andrew; Constable, Anne; Daneshian, Mardas; Edwards, Gareth; Garthoff, Jossie A.; Jeffery, Brett; Krul, Cyrille; Schuermans, Jeroen
Abstract: Toxicology and safety assessment are changing and require new strategies for evaluating risk that are less depending on apical toxicity endpoints in animal models and relying more on knowledge of the mechanism of toxicity. This manuscript describes a number of developments that could contribute to this change and implement this in a stepwise roadmap that can be applied for the evaluation of food and food ingredients. The roadmap was evaluated in four case studies by using literature and existing data. This preliminary evaluation was shown to be useful. However, this experience should be extended by including examples where experimental work needs to be included. To further implement these new insights in toxicology and safety assessment for the area of food and food ingredients, the recommendation is that stakeholders take action in addressing gaps in our knowledge, e.g. with regard to the applicability of the roadmap for mixtures and food matrices. Further development of the threshold of toxicological concern is needed, as well as cooperation with other sectors where similar schemes are under development. Moreover, a more comprehensive evaluation of the roadmap, also including the identification of the need for in vitro experimental work is recommended. Highlights: A new strategy for food and food ingredients safety assessment is presented in a roadmap format. This roadmap is focussing on mechanisms of toxicity rather than apical endpoints in animal studies. The usefulness of this roadmap was evaluated in four case studies using literature and existing data. Recommendations for stakeholder parties in the area of safety evaluation are proposed. A more comprehensive evaluation of the roadmap, including the need for in vitro experimental work, is recommended.